Transnational mothering: some observations from Asia, Sri Lanka Journal of Population Studies - Ukwatta, S; Hugo, G (My University, 2007)
Sri Lanka is seen as a country of growing numbers of transnational families with mothers being absent for a significant part of the growing up of their children with the increasing involvement of Sri Lankan women in overseas employment as domestic workers. The majority of these migrant women are married and have at least one child, and leave their children behind with other family members at home. While they usually arrange to accommodate the spatial and temporal separation forced by migration, this poses challenges to both mothers who migrate and their children left behind. The social and emotional ramifications of mothering from a distance, and how mothers cope with these problems are remained inadequately investigated in Sri Lanka. This paper examines this issue using the data collected in a survey of 400 migrant families and focus group discussions conducted in Sri Lanka in 2008. While the education of children is positively affected by their mothers’ migration, they also experience several negative effects. However, mother’s absence does not always have negative consequences on children due to two reasons. Firstly, many of the mothers do not totally abandon their children but continue to take the responsibility of childcare from abroad. Transnational communication is one of the methods used by these women to maintain intimacy with their children. Secondly, many migrant families are able to cope with the challenges of family separation with the support of family members. I illustrate the importance of investigating the issue first, explaining the background information of migrant families and motivations for their migration as a survival strategy. The methodology used in the study is then explained. Next, I explain the consequences of mothers’ migration on children left behind and how these mothers negotiate care work from a distance. Finally, the perceptions of female migrants and their family members on migration of women are discussed followed by a discussion of policy implications.